A Facile Fabrication and Transfer Method of Vertically Aligned Carbon Nanotubes on a Mo/Ni Bilayer for Wearable Energy Devices. Issue 8 (8th March 2020) - Lim, Chanhyuk; Shin, Yoonsoo; Hong, Seungki; Lee, Sangkyu; Kim, Dae‐Hyeong
Abstract: Carbon nanotubes are a promising material for flexible/wearable electrochemical device due to their mechanical softness, chemical stability, and high conductivity. Furthermore, the vertically aligned form of carbon nanotubes (VACNTs) have a large surface area due to their unique three‐dimensional (3D) nanostructure. Thus, VACNTs are particularly useful for wearable electrochemical sensors and/or energy devices. However, VACNTs are generally grown via a high‐temperature chemical vapor deposition process, which requires a rigid substrate. As a flexible/wearable device platform, therefore, VACNTs should be transferred from rigid substrates to soft substrates. Here, a facile fabrication and transfer method of a unique 3D nanostructure, that is, VACNTs on the Mo/Ni bilayer, for high performance flexible/wearable devices is reported. After growth of VACNTs on a Mo/Ni bilayer, VACNTs with the Mo/Ni bilayer can be easily peeled‐off from the SiO2 wafer by using weak adhesion of Ni to SiO2 for transfer printing onto polymeric/elastomeric substrates. Moreover, the Mo layer helps facile growth of VACNTs, and the Mo/Ni bilayer underneath VACNTs maximizes the lateral current flow. The proposed 3D nanostructure (VACNTs on the Mo/Ni bilayer) is successfully applied as flexible electrodes for high‐performance wearable asymmetric supercapacitors. Abstract : Vertically aligned carbon nanotubes on a Mo/Ni bilayer is peeled off from the wafer by using the weak adhesion, and transferred on a flexible substrate for wearable system. Electrons can be vertically transported through the nanotubes (vertical conduction) and transported to external circuits through metal layers (lateral conduction). By utilizing the 3D nanostructure, the wearable energy storage device is demonstrated.